Relapsed Plasmablastic Lymphoma in an HIV-Infected Patient—Experience of High-Dose Chemotherapy with Autologous Stem Cell Rescue: A Case Report with Review of Literature - M., Ganapathi Bhat; Jain, Reetu; Shah, Samir S.; Shaikh, Fahad Afzal (Indian Journal of Medical and Paediatric Oncology, 2022)
Plasmablastic lymphoma (PBL) is a subtype of non-Hodgkin lymphoma with dismal outcome despite multidrug chemotherapy regimen leading to high rates of disease recurrence. High-dose chemotherapy with autologous stem cell rescue (HDCT/ASCR) is an effective salvage therapy in patients with chemo-sensitive human immunodeficiency virus (HIV)-associated non-Hodgkin lymphoma. We report a case of 38 years old male with relapsed PBL associated with underlying HIV infection, who underwent HDCT/ASCR. He presented with low-grade fever and abdominal discomfort. He was evaluated with fluorodeoxyglucose positron emission tomography scan followed by omental biopsy that confirmed disease relapse. He received second-line therapy containing bortezomib and daratumumab and achieved remission (CR2). Subsequently, he underwent HDCT/ASCR. He has been clinically asymptomatic in good general condition having disease-free survival of 18 months after HDCT/ASCR. Our objective of presenting this case report is its complexity from presentation, diagnosis, and treatment. We take this opportunity to review the epidemiology and clinicopathological characteristics of PBL, as well as discuss the advancements in therapeutic options of this challenging disease.
Keywords: plasmablastic lymphoma; HIV infection; combined antiretroviral therapy; autologous stem cell transplant